EFEKTIVITAS PEMBERIAN KESEHATAN THE HEALTH BELIEF MODEL TERHADAP PENGETAHUAN KELUARGA TENTANG TB PARU DI RS TNI AL Dr. KOMANG MAKES BELAWAN - Christina Magdalena T. Bolon; Viska Renata Pasaribu; Rostinah Manurung; Paskah Rina Situmorang (Jurnal Ilmiah Keperawatan IMELDA, 2021)
Pulmonary tuberculosis (TB) is an infectious disease in the lungs caused by bacteria, namely Mycobacterium tuberculosis. The number of pulmonary TB cases in Dr. Komang Makes Belawan as many as 23 patients. The high number of morbid cases is thought to have a lack of family understanding of TB sufferers regarding the concept of prevention and treatment of pulmonary tuberculosis accompanied by ineffective implementation of education by nurses. The research objective was to determine the effectiveness of health provision by applying The Health Belief Model to the knowledge of families with pulmonary tuberculosis. This research was conducted at the TNI AL Dr. Komang Makes Belawan was conducted starting July 2020. This type of research was a quasi-experimental design with a pre-test-post-test without a control group design. The population was 23 people with pulmonary tuberculosis patients and all of them were used as research samples. The results showed that the average score of knowledge before being given health education by implementing the Health Belief Model with leafelt (intervention) counseling was 11.47 and increased to 15.00 after the intervention with an average of 3.53. The results of the paired t test analysis showed that health education with the application of The Health Belief Model was effective in increasing the knowledge of families with pulmonary tuberculosis with a p value of 0.000 <0.05. The conclusion is that there are differences in family knowledge about pulmonary TB before and after getting health education The Health Belief Model.